Model Based Controller With Internal Model Control (IMC) Which Tunning By Set Point and Disturbance on Power Plant Based HYSYS - Hendrik Elvian Gayuh Prasetya; Totok R. Biyanto (Institut Teknologi Sepuluh Nopember, 2015)
Waste heat recovery generation (WHRG) is a power plant systems which utilize waste gas in process of industrie. To design plant of WHRG need right control parameters for maintain heat and mass balance. The control technique of PID is the methode usually used in all industrie by doing tunning based of changes set point changes. In fact, not only based on the change of set point tunning can generate proper response, but the value based on disturbance change of tunning is also appropriate for used. This is due to value based on tunning disturbance can reduce the nuisance value of direct entry at the output of the process. The tunning of the set point value is given i.e. ± 5%, ± 10% and ± 15% of the design data are used, whereas for tunning of disturbance value that is used i.e., ± 5% of the value of the input parameter used as a disturbance. Based on the resulting control response indicates that the method for use to control the tunning disturbance in this research, it is not appropriate to be applied using methods of IMC-PID. This is due to the characteristics of the resulting response indicates a value that is less good.